Pengertian Agen Perubahan Dalam Pengembangan Organisasi di SDN 20 Indarung , Kota Padang - Rahmatul okta fiani (CV. ITTC INDONESIA, 2025)
Change is an inevitable aspect of life in society, organizations, and the workplace, including within the educational environment. In this context, the role of change agents is crucial as they act as drivers, facilitators, and implementers of transformation to move organizations toward improvement. This study aims to explore the concept of change agents and their roles in improving the quality of educational services in schools. The research employs a descriptive qualitative approach with data collected through observation and interviews conducted in several schools, namely SDN 20 Indarung, SDN 24 Parupuk Tabing, SD IT Karakter Anak Shalih, SMP Negeri 7 Padang, SDN 05 Air Tawar Barat, and SMP 1 Padang Panjang. The results indicate that change agents are not limited to individuals in formal positions but can be anyone with the willingness and ability to create positive change. They play an essential role in accelerating school administrative digitalization, fostering teacher collaboration, cultivating a culture of innovation, and improving work efficiency. Therefore, change agents contribute significantly to building adaptive, effective, and quality-oriented educational environments.